Hungarian Monitoring, 19 September 1990 . [Magyar rádiófigyelő], 1990. szeptember 19 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - European colloquium roundtable - Malév Hungarian Airlines takes part in an aid shipment to Kuwait - UN Security Council on tightening the embargo against Iraq - US reduces the size of its armed forces stationed abroad - Moscow stock exchange opens Domestic Affairs: - Thatcher visits Budapest - Otto Habsburg in talks in Budapest - József Antall meets Radio Free Europe supervisory board - Hungarian education in Romania Külpolitika: - Európa-kollokvium kerekasztal - Malév-részvétel egy kuvaiti segélyszállítmánynál - A BT az Irak elleni embargó szigorításáról - Az Egyesült Államok csökkenti a külföldön állomásozó haderők méretét - Megnyílt a moszkvai tőzsde Belpolitika: - Thatcher budapesti látogatása - Habsburg Ottó Budapesten tárgyal - Antall József találkozója a SZER felügyelő-bizottságával - A romániai magyar oktatás helyzete